Arnold O. Beckman receiving the California Industrialist of the Year Award - Crest Photography (1971)
This award was given by the California Museum of Science and Industry. Dr. Beckman is on the right; the other two men in this photograph are unidentified. Dr. Arnold O. Beckman (1900-2004) invented the first commercially successful electric pH meter in 1934 and thus began a long career manufacturing scientific and medical instruments with National Technical Laboratories, Arnold O. Beckman, Inc., and Beckman Instruments. After his retirement he devoted his life to philanthropy and specifically supporting scientific innovation.
Keywords: Beckman, Arnold O.; California Museum of Science and Industry; Awards